Analisis Pemikiran Asy-Syafi’iyah dalam Berkurban pada Masa Wabah Penyakit Mulut dan Kuku (PMK) di Madura - Ach. Faisol (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Madura is one of the areas exposed to the Foot and Mouth Disease (FMD) virus which infects livestock with even hooves such as cows, goats, and the like. In connection with this spread, a question arises as to whether the people of Madura are still subject to the recommended order to perform sacrifices, seeing that the virus is still attacking in the month of Dzulhijjah. This problem is then studied from the thinking of the Ash-Syafi'iyah Ulama considering that the majority of Madurese people adhere to the Shafi'i school of thought. At its stage the research was approached by descriptive descriptive research with data sources from as-Syafi'iyah books and the state of the spread of the virus in Madura. The data findings are processed into a description to facilitate the analysis process. It was found that the sunnah of sacrificing is still recommended for Madurese people who can afford it provided that the livestock to be used as sacrifices are not disabled, including defects caused by infection with the FMD virus with severe symptoms. You can also take an alternative using goats or sheep as sacrificial animals because the infection virus in both is not as much as in cows. Or you can also get around this by buying sacrificial animals when it is nearing the time of their slaughter, so that it will be safer